The Plant Invertase/Pectin Methylesterase Inhibitor Superfamily - Coculo, Daniele; Lionetti, Vincenzo (Frontiers in Plant Science, 2022)
Invertases (INVs) and Pectin Methylesterases (PMEs) are essential enzymes coordinating carbohydrate metabolism, stress responses and sugar signaling. INVs catalyzes the cleavage of sucrose into glucose and fructose, exerting a pivotal role in sucrose metabolism, cellulose biosynthesis, nitrogen uptake and reactive oxygen species scavenging as well as osmotic stress adaptation. PMEs exert a dynamic control of pectin methylesterification to manage cell adhesion, cell wall porosity and elasticity, as well as perception and signaling of stresses. INV and PME activities can be regulated by specific proteinaceous inhibitors, named INV inhibitors (INVIs) and PME Inhibitors (PMEIs), share several structural properties, show low aa sequence identity Despite being targeted by different enzymes, INVIs and PMEIs belong to the same large protein family named “plant invertase/pectin methyl esterase inhibitor superfamily”. They share two disulfide bridges, that are mainly alpha-helical, and both form a non-covalent 1:1 complex with their enzymatic counterpart. Some PMEI members are organized in a gene cluster with specific PMEs. Although the most important physiological information was obtained in Arabidopsis thaliana, there are now several characterized INVI/PMEIs in different plant species. Here, we reviewed the current knowledge on all the isoforms belonging to this fascinating family, from the specific activity of characterized isoforms to their functions in plant physiology. A review of the nomenclature of some isoforms belonging to the family is presented. The features of INVI/PMEIs are discussed in view of their potential biotechnological applications.